A Network Comparison on Safety Profiling of Immune Checkpoint Inhibitors in Advanced Lung Cancer - Yan, Yi-Dan; Cui, Jiu-Jie; Fu, Jie; Su, Ying-Jie; Chen, Xiao-Yu; Gu, Zhi-Chun; Lin, Hou-Wen (Frontiers in Immunology, 2021)
Background: Immune checkpoint inhibitors (ICIs) have become one of the standard treatment options for advanced lung cancer. However, adverse events (AEs), particularly immune–related AEs (irAEs), caused by these drugs have aroused public attention. The current network meta-analysis (NMA) aimed to compare the risk of AEs across different ICI–based regimens in patients with advanced lung cancer. Methods: We systematically searched the PubMed, EMBASE, and Cochrane Library databases for relevant randomized controlled trials (RCTs) that compared two or more treatments, with at least one ICI administered to patients with advanced lung cancer. The primary outcomes were treatment–related AEs and irAEs, including grade 1–5 and grade 3–5. The secondary outcomes were grade 1–5 and grade 3–5 irAEs in specific organs. Both pairwise and network meta-analyses were conducted for chemotherapy, ICI monotherapy, ICI monotherapy + chemotherapy, dual ICIs therapy, and dual ICIs + chemotherapy for all safety outcomes. Node–splitting analyses were performed to test inconsistencies in network. Sensitivity analyses were adopted by restricting phase III RCTs and studies that enrolled patients with non–small cell lung cancer. Results: Overall, 38 RCTs involving 22,178 patients with advanced lung cancer were enrolled. Both pooled incidence and NMA indicated that treatments containing chemotherapy increased the risk of treatment–related AEs with mono or dual ICI regimens. However, contradicting results were observed for grade 1–5 irAEs: dual ICIs + chemotherapy was associated with the worst ranking (probability: 50.5%), followed by therapy with dual ICIs (47.2%), ICI monotherapy (80.0%), ICI monotherapy + chemotherapy (98.0%), and finally chemotherapy (100.0%). In addition, subtle differences were observed in grade 3–5 irAEs; when ranked from least safe to safest, the trend was dual ICIs therapy (60.4%), dual ICIs + chemotherapy (42.5%), ICI monotherapy (76.3%), ICI monotherapy + chemotherapy (95.0%), and chemotherapy (100.0%). Furthermore, detailed comparisons between ICI–based options provided irAE profiles based on specific organ/system and severity. Conclusions: Among existing ICI–based treatment options, ICI monotherapy + chemotherapy might be a better choice for advanced lung cancer, considering their overall immune–related safety profiles. The safety profiles of ICI–based treatments are modulated by specific irAEs and their severity.